2016
DOI: 10.1002/jmv.24524
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Epstein–Barr virus Rta promoter in EBV primary infection, reactivation and lymphoproliferation

Abstract: During Epstein-Barr virus (EBV) latency, the EBV genome is largely silenced by methylation. This silencing is overturned during the switch to the lytic cycle. A key event is the production of the viral protein Zta which binds to three Zta-response elements (ZRE) from the Rta promoter (Rp), two of which (ZRE2 and ZRE3) include three CpG motifs methylated in the latent genome. The bisulphite pyrosequencing reaction was used to quantify the methylation of ZRE2, ZRE3a, and ZRE3b in EBV-positive cell lines and in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Some studies have reported that the methylation status of the EBV promoter is related to the activation of the latent promoter. The EBV genome is unmethylated but becomes heavily methylated during the latent stage of the virus cycle in infected cells (Germi et al 2016 ). How EBV promoters obtain methylated cytosines is not yet clear; once established, this methylation pattern is maintained in proliferating and latently infected cells (Kalla et al 2012 ).…”
Section: Dna Methylation Of the Ebv Genomementioning
confidence: 99%
“…Some studies have reported that the methylation status of the EBV promoter is related to the activation of the latent promoter. The EBV genome is unmethylated but becomes heavily methylated during the latent stage of the virus cycle in infected cells (Germi et al 2016 ). How EBV promoters obtain methylated cytosines is not yet clear; once established, this methylation pattern is maintained in proliferating and latently infected cells (Kalla et al 2012 ).…”
Section: Dna Methylation Of the Ebv Genomementioning
confidence: 99%
“…On the other hand, since EBV infection is very common, the presence of NA IgG and EBV DNA may be reactivation infection, secondary infection or superinfection, which could not be distinguished in this study. According to previous studies, 17,31,32 we regarded the presence of NA IgG and EBV DNA as reactivation infection.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, 17,31,32 we regarded the presence of NA IgG and EBV DNA as reactivation infection.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Currently, no straightforward technique is available to differentiate the intracellular episomal genome (found in latent infections and lymphoproliferations) from the viral linear genome (present in productive infections). Several studies suggest that the evaluation of EBV genome methylation may be an interesting tool, as low methylation levels point to a productive replication process, whereas high methylation levels indicate a latent/proliferative process [ 123 , 127 , 128 ]. This will be detailed in the final section below.…”
Section: Ebv-associated Malignanciesmentioning
confidence: 99%
“…EBV DNA methylation patterns varied according to the EBV-associated disease under consideration, which could differ between healthy individuals and patients with NPC [ 168 ]. A number of studies analyzing the whole virus methylome or a single gene methylation, showed that EBV methylation was lower in non-malignant tissue biopsies than in malignant tumor biopsies [ 123 , 128 , 169 , 170 ]. Lam et al developed a combined approach of plasma EBV DNA analysis, including the plasma EBV DNA methylome, and the use of the fractional concentration and size of plasma EBV DNA for NPC diagnosis.…”
Section: Sequencing Next-generation Sequencing and New Ebv Markersmentioning
confidence: 99%